ISOLASI GEN SITRAT SINTASE BAKTERI Pseudomonas aerugenosa PS2 DARI RIZOSFER POHON KRUING (Dipterocarpus sp.) UNTUK MODEL KONSTRUKSI METABOLISME SEL MIKROALGA BERKARBOHIDRAT RENDAH - Susilaningsih, Dwi; Umoro, Asahedi; Ochieng, Fredrick Onyango; Widyaningrum, Dian Noverita; Susanti, Hani; Susilo, Hadi; Swastika, I Nengah; Widyastuti, Utut (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Pseudomonas has the potential ability for production of citrate synthase synthesis. Pseudomonas aeruginosa could synthesize the enzyme of citrate synthase which is most likely compatible with microalgae cell. Pseudomonas aerugenosa can be found in the rhizosphere of Kruing (Dipterocarpus sp., Dipterocarpaceae). This bacteria is commonly used in agriculture purposes because it is able to synthesize organic acid such as citric acid. These organic acids are synthesized from a reaction between oxaloacetate and acetyl CoA, catalyzed by citrate synthase (CS) in the tricarboxylic acid cycle (TCA). Rhizosphere as microbial sources was obtained from Kruing (Dipterocarpus sp.), which was collected from ?Carita? Research Forest, Pandeglang, Banten, West Java. Citrate synthase gene-specific primers were designed based on citrate synthase gene sequences as depicted in Genbank. The isolation and amplification showed that citrate synthase can be detected and purified from Pseudomonas aeruginosa target and it consists of 1600 bp and encodes 509 amino acids. Based on BLAST (Basic Local Alignment Search Tool) analysis, CS genes that were successfully isolated had 92 % similarity with Pseudomonas aeruginosa type II citrate synthase. This CS gene is expected to be expressed in microalgae metabolism to divert the metabolism of carbohydrate formation into fatty acids.